RADT-13. CLINICAL OUTCOMES COMPARING RADIOSURGERY TECHNIQUES FOR MANAGING LARGE BRAIN METASTASES. (14th November 2022) - Kutuk, Tugce; Kotecha, Rupesh; Tolakanahalli, Ranjini; Appel, Haley; Hall, Matthew; Wieczorek, D Jay; Lee, Yongsook; McDermott, Michael; Ahluwalia, Manmeet; Gutierrez, Alonso; Mehta, Minesh; Tom, Martin
Abstract: INTRODUCTION: Large brain metastases (BM) are associated with poor local control with single-fraction radiosurgery (SRS) alone. We sought to compare outcomes with various alternative management strategies to assess disease control rates. METHODS: Consecutive patients diagnosed with BM ≥ 2 cm in maximum diameter between 3/2019-2/2021 and treated at a single tertiary institution were included. Primary endpoints included freedom-from-local-failure (FFLF) calculated on a per-lesion basis from the date of initial intervention to local failure, and overall survival (OS). Kaplan-Meier analysis and the log-rank test were used. RESULTS: 86 patients with 102 large BM met inclusion criteria. The median age was 66 years (range: 31-98), median KPS was 90 (50-100), and 57.8% were female. The most common primary tumor was lung in 40 (39.2%) lesions. The median tumor volume was 9.7 cm 3 (2.1-35.5 cm 3 ) and the median maximum tumor diameter was 3.3 cm (2.9-5.6 cm). 37 (36.3%) lesions were treated with staged-SRS, 31 (30.4%) with resection and postoperative-SRS, 21 (20.6%) with preoperative-SRS and resection, and 13 (12.7%) with fractionated-SRS (FSRS). Lesions treated with preoperative-SRS or postoperative-SRS were associated with higher rates of no- or stable-extracranial disease, and larger tumor volumes (preoperative-SRS: median 14.5 cm 3 [4.2-33.1]; postoperative-SRS: 18.0 cm 3 [2.5-35.5]; FSRS: 5.9 cm 3 [2.1-24.6]; staged-SRS: 6.5 cm 3 [2.2-27.8]).With a median follow-up of 15.6 months, 12 (11.8%) local failures and 42 (41.2%) deaths occurred. 1-year FFLF and OS for entire cohort were 85.6% (95% CI: 77.9-93.3%) and 64.4% (95% CI: 54.7-74.1%), respectively. The 1-year FFLF (p=0.542)/OS (p=0.043) rates were 94.1%/100% for preoperative-SRS, 84.0%/43.4% for staged-SRS, 81.8%/74.1% for FSRS, and 81.5%/63.4% for postoperative-SRS, respectively. CONCLUSION: Although limited by patient numbers, selection bias, and high attrition rate, preoperative-SRS had the numerically most favorable outcomes, supporting this approach for large BM. Prospective evaluation is warranted to determine the optimal management strategy.